Uniparental inheritance of cpDNA and the genetic control of sexual differentiation in Chlamydomonas reinhardtii - Nishimura, Y., Kyoto Univ. (Japan) (Journal of plant research, 2010)
An intriguing feature of most eukaryotes is that chloroplast (cp) and mitochondrial (mt) genomes are inherited almost exclusively from one parent. Uniparental inheritance of cp/mt genomes was long thought to be a passive outcome, based on the fact that eggs contain multiple numbers of organelles, while male gametes contribute, at best, only a few cp/mtDNA. However, the process is likely to be more dynamic because uniparental inheritance occurs in organisms that produce gametes of identical sizes (isogamous). In Chlamydomonas reinhardtii, the uniparental inheritance of cp/mt genomes is achieved by a series of mating type-controlled events that actively eliminate the mating type minus (mt-) cpDNA. The method by which Chlamydomonas selectively degrades mt, cpDNA has long fascinated researchers, and is the subject of this review.